Pemberdayaan Masyarakat Melalui Kerajinan Batik Jumputan Gambo di Desa Toman Kecamatan Babat Toman Kabupaten Musi Banyuasin - Oktanedi, Aldri; Hendarso, Yoyok; Saptawan, Ardiyan (Turast: Jurnal Penelitian dan Pengabdian, 2023)
This research examines the process of community empowerment through the craft of Batik Jumputan Gambo in Toman Village. This research approach uses qualitative-descriptive research. While the data collection method is done by purposive sampling. The results of this study indicate that the process of community empowerment through the craft of Batik Jumputan Gambo in Toman Village, Babat Toman Sub-district, Musi Banyuasin Regency includes 3 stages of empowerment, namely the awareness stage, the capacity stage and the empowerment stage. Supporting factors for empowerment through batik handicrafts in Toman Village are support from the Musi Banyuasin Regency government in the form of: training, promotion and marketing; and ease of obtaining raw materials for natural coloring of gambier sap waste. The inhibiting factors are the lack of ability of craftsmen in promoting batik production; the weak ability of craftsmen in doing creativity and modification of batik motifs in accordance with market tastes; and limitations on the procurement of capital to develop batik businesses. For this reason, the suggestion that can be given is to improve the ability of Gambo Jumputan Batik craftsmen which includes increasing creativity and innovation.